NILAI-NILAI RELIGIUS DALAM NOVEL KETIKA TUHAN JATUH CINTA KARYA WAHYU SUJANI - Saputri, Riva; Nurizzati, Nurizzati (Jurnal Bahasa dan Sastra, 2019)
This study aims to describe the religious values related to creed, sharia, and morals depicted in the speech and behavior of the characters in the novel Ketika Tuhan Jatuh Cinta by Wahyu Sujani. This type of research is a qualitative research with descriptive methods. The research instrument is the researcher himself. Data collection is done by (1) reading the novel Ketika Tuhan Jatuh Cinta by Wahyu Sujani, carefully in order to understand the story and character of characters in the novel; (2) marking a part of the novel that contains religious values in the novel Ketika Tuhan Jatuh Cinta by Wahyu Sujani; (3) inventory of religious values data contained in the novel Ketika Tuhan Jatuh Cinta by Wahyu Sujani. The data validation technique used in this study is a detailed description technique. Analyzing the data is done by (1) identifying and classifying the data that has been collected to describe it as the aspect under study; (2) analyzing the data according to its categories; (3) interpret or interpret the data of religious values obtained; (4) conclude and write a research report. Based on the results of the study, the following matters can be concluded. (1) The religious values contained in the novel Ketika Tuhan Jatuh Cinta by Wahyu Sujani are (a) the values of faith, such as faith in God, faith in the Angels of God, faith in the book of God, faith in the apostles of God, faith in the day end, faith in Qada and Qadar; (b) sharia values, such as prayer, prayer, dhikr, dress, marriage; (c) moral values, such as morals to God, morals to families, morals to oneself, and morals to others: (2) Religious values depicted in character's speeches and behavior are (a) character's speech and narrator's speech; (b) the character's behavior towards God; character's behavior towards family; the character's behavior towards himself; character's behavior towards others.